2000
DOI: 10.1515/jgth.2000.017
|View full text |Cite
|
Sign up to set email alerts
|

Tree actions of automorphism groups

Abstract: We introduce conditions on a group action on a tree that are su½cient for the action to extend to the automorphism group. We apply this to two di¨erent classes of one-relator groups: certain Baumslag±Solitar groups and one-relator groups with centre. In each case we derive results about the automorphism group, and deduce that there are relatively few outer automorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 10 publications
2
37
0
Order By: Relevance
“…Building on work from Forester [11], Gilbert et al [14], Guirardel [15] and Pettet [30], it is shown in Levitt [23] that, if G is not solvable, T is rigid if and only if satisfies the following condition (see Figure 6): if e; f are distinct oriented edges of with the same origin v , and the label of f near v divides that of e , then either e D x f is a .p;˙p/-loop with p 2, or v has valence 3 and bounds a .1;˙1/-loop.…”
Section: Collapses and Algebraic Rigiditymentioning
confidence: 99%
“…Building on work from Forester [11], Gilbert et al [14], Guirardel [15] and Pettet [30], it is shown in Levitt [23] that, if G is not solvable, T is rigid if and only if satisfies the following condition (see Figure 6): if e; f are distinct oriented edges of with the same origin v , and the label of f near v divides that of e , then either e D x f is a .p;˙p/-loop with p 2, or v has valence 3 and bounds a .1;˙1/-loop.…”
Section: Collapses and Algebraic Rigiditymentioning
confidence: 99%
“…It can also happen that there is only one reduced graph, or finitely many. In these latter cases, useful information about Out.G/ can be obtained, as in Gilbert-Howie-Metaftsis-Raptis [8], Pettet [15] and Levitt [13]. Other aspects of GBS groups have been studied by Kropholler, Whyte, Levitt and others.…”
Section: Introductionmentioning
confidence: 95%
“…The strongly-slide free condition gives the following fact (see [7]): Lemma 2.1 Assume that e 1 , e 2 ∈ E(T ) are two edges sharing a common vertex v and that f (e 1 ) ∩ f (e 2 ) is not reduced to one point. Then e 1 and e 2 are in the same G v -orbit and f (e 1 ) ∩ f (e 2 ) is strictly contained in f (e 1 ) (resp.…”
Section: Let's Now Define a G-equivariant Map F : T → T For Each Vementioning
confidence: 99%